Integrasi Nilai Budaya Keluarga ke Dalam Pembelajaran Sekolah: Studi Kasus pada Siswa Multikultural di Kota Mataram - Irfan, Moh.; Wijaya, Herman (Kasta: Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2024)
This study aims to examine how family cultural values are integrated into school learning processes within the context of multicultural students in the city of Mataram. Using a descriptive qualitative approach and a case study design in selected primary and secondary schools, the research explores teachers’ strategies, parental involvement, and school environment dynamics in embedding local cultural values into the curriculum and instructional practices. The findings reveal that integrating family cultural values—such as mutual cooperation, respect for elders, and social responsibility—can significantly enhance student character development and build a meaningful bridge between home and school life. Effective strategies include contextual learning, cultural dialogue, and active parental participation in school activities. However, the implementation of such integration faces structural challenges, including limited policy support, insufficient teacher training, and a lack of local-based learning resources. Therefore, systemic support from schools and educational authorities is needed to promote a more culturally responsive education within multicultural communities.